Ashwat's Teaching Strategies and Their Implications In The Learning of Maharah Istima' - Imawan, Yuli; Rahmatan, Madah; Hania, Irfan; Alimudin, Alimudin (International Journal of Education and Teaching Zone, 2023)
One component of the language that Arabic learners first face is ashwat or sound. with sound teaching strategies that the teacher does correctly and precisely, will help students overcome difficulties in learning ashwat arabiyah. mastery of language sounds becomes important, because sounds are the basic thing for mastering listening skills. Therefore, the purpose of this study is to describe the strategies and steps of teaching ashwat arabiyah and their influence on the mastery of maharah istima'. Using a descriptive-qualitative design, this study reveals three basic steps in ashwat teaching, namely: presentation of pronunciation models, giving exercises/drills, and practicing language use. as for The teaching of language sounds is the most basic activity to develop listening skills. there are five phases of listening learning, including; Phase recognition, initial comprehension, mid-comprehension, advanced comprehension and Assessment/taqwim. there are 13 steps of listening learning related to ashwat teaching, including hearing and saying, listening-writing (dictation), listening-doing, hearing-guessing, expanding sentences, finding objects, whispering chains, completing stories, identifying keywords, identifying topic sentences, abbreviating/summarizing, paraphrases, and answering questions.